'No one likes a grass' Female police officers' experience of workplace sexual harassment: A qualitative study. (June 2023) - Davis, Hannah; Lawrence, Sophie; Wilson, Emily; Sweeting, Fay; Poate-Joyner, Annabel
Sexual harassment is multifaceted and complicated, creating a hostile environment dominated by sexually motivated behaviours. It is experienced by many, particularly in the workplace. For example, many police officers experience sexual harassment from a colleague. Despite this, sexual harassment remains under-researched, with limited exploration into victims' experiences first-hand. As such, the current study aimed to research female police officers' experiences of sexual harassment by colleagues to investigate risk factors of sexual harassment and barriers to reporting. Seven transcripts were collected using semi-structured interviews, both in-person and online. Despite the assurance of anonymity, officers feared coming forward for research owing to identification concerns. Interpretative phenomenological analysis was used for the analysis to extract in-depth accounts from participants. Results showed that police culture contributed significantly to facilitating sexual harassment. For example, a male-dominant force, a hierarchical structure and the blue wall of silence. In addition, participants faced barriers to reporting sexual harassment. For example, a rumour mill culture and oppositional reactions from colleagues. Furthermore, the sexual harassment that the participants faced negatively affected their attitudes to work, and their physical and mental health.